The Rat Lodge Revisited - Galaburri, R.W. (ARCTIC, 1991)
[A mystery remains surrounding George Back's placement of Rat Lodge on the west side of Artillery Lake at latitude 63 01 45 N, just slightly north of the Beaver Lodge, which sits at 63 N exactly.] . Rat Lodge is not found opposite the Beaver Lodge, as shown on topographic maps. Its position is 16 km south, by the entrance to Timber Bay. The folded map in George Back's narrative does not clearly show where the lodge is situated and in the book the explorer makes it seem that both lodges are visible at the same time. From the two false Rat Lodge sites one cannot distinguish the Beaver Lodge (Artillery Lake is 6.5 km wide at the 63rd parrallel), nor of course can it be seen from the true site of the Rat Lodge; but if the Beaver Lodge was also located in the latitude of Timber Bay, where the lake is only 3.2 km wide, then perhaps on a clear day one would be able to sight both lodges from the middle of the lake. This is not to suggest that the Beaver Lodge is actually so situated. Rat Lodge is distinct and Beaver Lodge is about 16 km away.